Instagram social media development strategy for promotional facilities and local wisdom potential in ecotourism-based coffee villages in Mekarbuana Village Karawang - Zenita Apriani; Ery Rosmawati; Dini Yani (Pusat Riset dan Inovasi Nasional, 2023)
Utilization and use of social media, especially Instagram as something common thing _ used many people for share things in nature positive . Sangabuana Karawang coffee village is one of the areas that save beauty nature , so therefore as aim tourism , whose potential no only for visitors local , however can also be developed for traveler foreign . Adapan aim study this is for reviewing the development strategy for Coffee - Based Villages Ecotourism in Mekarbuana Village , Karawang. As well as reviewing the strategy matrix SWOT analysis ( Strength , Weakness, Opportunity and Threat). Then followed by local coffee village managers . 1) How how to copywriting 2) when perfect time _ in promotion on social media 3) how method make market. Method used that is approach characteristic persuasive educative with lectures , discussions . Expected results form understanding and skills startgi in use social media for promotion development of the Sangabuana coffee village .